Overview of the Average Amount of Fluid Expelled by Patients Undergoing Continuous Ambulatory Peritoneal Dialysis Therapy for The Last 3 Month and Its Review According to the Islamic View - Auliannisa Ramadhani; Linda Armelia; Muhammad Arsyad (Junior Medical Journal, 2022)
Chronic kidney disease (CKD) is a clinical condition characterized by a slowly progressive and permanent decline in kidney function. One of the renal failure therapy facilities that can be chosen is Continuous Ambulatory Peritoneal Dialysis (CAPD). Patients with CAPD can perform dialysis independently, but there are several factors that affect the ability in CAPD so that the balance of the amount of dialysate fluid expenditure is disturbed. Therefore, a study was conducted to determine the effectiveness of CAPD therapy based on a review of the average amount of fluid released during therapy during the last 3 months This retrospective study was a descriptive cross-sectional study using a consecutive sampling technique, where the researcher reviewed primary data based on respondents' answers to the questionnaire and secondary data from the CAPD therapy patient diary. The results showed Based on demographic analysis we can conclude that 27 respondents (60%) are male, 43 respondents (95.56%) were in the age range 20-60 years, 42 respondents (93.33%) were Muslim, 30 respondents (66.6%) are Javanese, 21 respondents (46.7%) have a high school education, 23 respondents (51.11%) are workers with 24 respondents (53.3%) not willing to answer the income earned for a month. The average weight and height of the respondents respectively was 66.67 kg (SD 12.8) and 163.69 cm (SD 7.39). Analysis of the characteristics of respondents' CAPD therapy found 22 respondents (48.89%) had undergone therapy for 1-3 years, 39 respondents (86.67%) used combination fluids with 23 respondents excreting an average of 800-1000 fluids per day. 29 respondents (64%) admitted had experienced the amount of fluid that came out less with the most felt symptom was edema (31%). On the other hand, 38 respondents (84.4%) claimed to have experienced more fluid discharge with no symptoms (79%).